Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 23



Work Step by Step

RECALL: $(F-G)(x) = F(x) - G(x)$ Using the formula above gives: $(F-G)(x) \\= F(x)-G(x) \\=(x^2-2)-(5-x) \\=x^2-2-5-(-x) \\=x^2-7+x \\=x^2+x-7$ To find $(F-G)(3)$, substitute $3$ to $x$ in the equation above to obtain: $(F-G)(x) = x^2+x-7 \\(F-G)(3) = 3^2+3-7 \\(F-G)(3)=9+3-7 \\(F-G)(3)=12-7 \\(F-G)(3)=5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.